DIGITALIZATION OF JUDICIARY: INFORMATION MODEL FOR ASSESSING THE DEGREE OF PUBLIC DANGER OF PRISONERS (Bulletin of criminological association of Ukraine, 2024)
The article applies a multidisciplinary approach that combines methods of information technology (IT) and legal science for processing and analyzing legal information. The aim is to obtain new knowledge for decision-making in criminal proceedings, particularly regarding determining the degree of threat to society posed by prisoners. The correspondence analysis method is used to identify the relationships between the level of danger to society, socio-demographic characteristics, and information about the convictions of convicts. It has been established that persons who were first convicted at a young age, have a low level of education, are unemployed or partially employed, were previously sentenced to a suspended sentence, and/or were suspended or released early, pose a greater risk to society. The obtained results can be used for making informed decisions by courts, probation bodies, and law enforcement agencies when determining the measure and term of punishment, determining the feasibility of early suspended release, and establishing additional restrictions or obligations for convicts after their release, effective organization of supervision and social support for released persons, developing strategies for prevention, prevention, and detection of repeated crimes. The proposed approach can contribute to ensuring a balance between protecting society, fair justice, and the reintegration of offenders.
Keywords: criminal justice; digitalization of court proceedings; justice; degree of danger; information model; decision-making; information technology; legal information analysis; data protection